Method for analyzing and detecting PFASs in environmental water sample

By using the metal organic framework material UiO-67-CH2-N(CH3)2, which is functionalized by tertiary amine, as a solid phase extraction adsorbent, combined with liquid chromatography-tandem mass spectrometry technology, the problem of low sensitivity and recovery in environmental water samples in the prior art was solved, and efficient and accurate PFASs analysis and detection were achieved.

CN119688877AActive Publication Date: 2025-03-25BIOTECH CENT OF SHANDONG ACAD OF SCI +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411891812.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

Existing solid-phase adsorbent materials cannot effectively meet the needs of detecting PFASs in environmental water samples, with low detection sensitivity and low recovery rate, resulting in poor detection effect.

Method used

UiO-67-CH2-N(CH3)2, a metal-organic framework material functionalized by tertiary amine, was used as a solid-phase extraction adsorbent, and PFASs were separated and enriched by efficient solid-phase extraction technology, and was detected in combination with liquid chromatography-tandem mass spectrometry.

Benefits of technology

Efficient extraction and enrichment of PFASs were achieved, and the accuracy and reproducibility of the analysis results were improved. The average recovery rate was 84.0-116.9%, and the relative standard deviations between day and day were between 0.13-7.04% and 1.88-8.18%, respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200829890000021
    Figure BDA0005200829890000021
  • Figure BDA0005200829890000111
    Figure BDA0005200829890000111
  • Figure BDA0005200829890000122
    Figure BDA0005200829890000122
Patent Text Reader

Abstract

The invention provides a method for analyzing and detecting PFASs in an environmental water sample. According to the analysis and detection method, after a tertiary amine functionalized metal organic framework material UiO-67-CH2-N (CH3) 2 is used as a solid phase extraction adsorbent for solid phase extraction, the solid phase extraction is combined with liquid chromatography-tandem mass spectrometry to detect PFASs in an environmental water sample. According to the method, the tertiary amine functionalized metal organic framework material (UiO-67-CH2-N (CH3) 2) is adopted as a solid phase extraction adsorbent, PFASs is efficiently separated and enriched, the extraction effect is good, the analysis result is accurate, and the reproducibility is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an analysis and detection method for PFASs in environmental water samples, and belongs to the field of analysis and detection. Background Art

[0002] In recent years, the emission of persistent organic pollutants into the environment has been increasing, and they have attracted widespread attention due to their toxic properties. Since 1950, perfluoroalkyl and polyfluoroalkyl substances (PFASs) have been used in various industrial and consumer products due to their chemical and thermal stability and unique surface properties. As an emerging persistent organic pollutant, PFASs are increasingly detected in food and environmental samples. Due to the persistence, bioaccumulation and toxicity of PFASs, they pose a significant impact on ecosystems and human health. In order to limit the use of PFASs, many governments and organizations have established more regulations. Therefore, the development of highly sensitive techniques is very important for monitoring PFASs in the environment at trace levels.

[0003] To date, high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS / MS) has been mainly used to identify and quantify PFASs in water samples. Considering the complex interferences in the samples and the trace or ultra-trace concentrations of PFASs, effective sample pretreatment of PFASs is crucial before analysis. Existing sample pretreatment techniques include solid phase extraction (SPE), liquid-liquid extraction, dispersed solid phase extraction (DSPE), solid phase microextraction (SPME), magnetic solid phase extraction (MSPE) and other pretreatment methods. Among them, SPE has the advantages of low organic solvent consumption, simple operation, high enrichment multiple, good recovery rate and reproducibility, and is widely used.

[0004] SPE adsorbents play a vital role in the extraction process. Due to the non-specific interactions between traditional adsorbents such as activated carbon and ion exchange polymers and PFASs, low enrichment efficiency and slow adsorption kinetics are exhibited. Therefore, the selection of suitable porous materials as adsorbents for SPE has become a research hotspot. Metal-organic frameworks (MOFs), covalent organic frameworks (COFs) and conjugated microporous polymers (CMPs) are emerging organic porous materials that have attracted much attention due to their high porosity, adjustable pore size, large specific surface area, adjustable chemical structure and properties, and physicochemical stability. MOFs are a class of highly crystalline porous materials assembled by metal ions or clusters and organic ligands through coordination bonds. They have the advantages of diverse composition structures, large specific surface area, adjustable pore size and easy post-modification. MOFs have shown excellent performance in the adsorption and removal of organic pollutants, and have become an ideal platform for removing PFASs from water environments. Among the existing MOFs, the UiO series MOFs formed based on metal zirconium (Zr) and organic carboxylic acid ligands have excellent stability in aqueous solution over a wide pH range, because there is a strong Zr(IV)-O bond between metal zirconium and organic ligands. Moreover, by designing organic carboxylic acid ligands containing specific functional groups, the functional groups are introduced into the framework of MOFs, and UiO series MOFs with specific functionality are synthesized, combining the advantages of functional groups and MOFs, thereby effectively improving their adsorption performance, which is of great significance for the analysis and determination of PFASs. For this reason, the present invention is proposed. Summary of the invention

[0005] In view of the shortcomings of the prior art, especially the inability of current solid-phase adsorption materials to meet the requirements for detecting perfluoroalkyl and polyfluoroalkyl pollutants (PFASs) in environmental water samples, low detection sensitivity, low recovery rate, and poor detection effect, the present invention provides a method for analyzing and detecting PFASs in environmental water samples. The method of the present invention uses a tertiary amine functionalized metal organic framework material (UiO-67-CH2-N(CH3)2) as a solid-phase extraction adsorbent to efficiently separate and enrich PFASs, with good extraction effect, accurate analysis results, and good reproducibility.

[0006] The technical solution of the present invention is as follows:

[0007] A method for analyzing and detecting PFASs in environmental water samples. The method uses a tertiary amine-functionalized metal organic framework material UiO-67-CH2-N(CH3)2 as a solid phase extraction adsorbent for solid phase extraction, and then combines it with liquid chromatography-tandem mass spectrometry to detect PFASs in environmental water samples.

[0008] According to the present invention, the structure of the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is shown as follows; the preparation method of the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3) is a prior art and can be prepared according to Chinese literature (Xi Fugui. Synthesis, modification and catalytic application of zirconium-based metal organic framework materials [D]. East China Normal University, 2016.);

[0009]

[0010] Preferably, the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3) is prepared according to the following method:

[0011] (1) Synthesis of methyl 4-bromo-3-diacetoxymethylbenzoate:

[0012] Take methyl 4-bromo-3-methylbenzoate (4.6 g, 20 mmol) and dissolve it in glacial acetic acid (33 mL) and acetic anhydride (34 mL), cool it to 0°C in an ice-water bath, add concentrated sulfuric acid (5 mL), slowly add chromium trioxide (6 g, 60 mmol), after the reaction is complete by thin-layer chromatography, slowly pour in a large amount of ice water (500 mL), oscillate with ultrasound for 2 h, collect the precipitated solid by filtration, wash the filter cake with water, and dry the solid at 70°C for 3 h to obtain a light yellow solid, which is methyl 4-bromo-3-diacetoxymethylbenzoate;

[0013] (2) Synthesis of methyl 4-bromo-3-formylbenzoate:

[0014] 4-bromo-3-diacetoxymethylbenzoic acid methyl ester (4.2 g, 11 mmol) was placed in a 250 mL eggplant-shaped bottle, and then THF (50 mL) and HCI (1N, 20 mL) were added in sequence. The reaction solution was stirred at 90°C under nitrogen protection, and the reaction was monitored by thin layer chromatography. When the raw material point disappeared, the reaction was stopped, and the mixture was distilled under reduced pressure. The obtained mixture was dissolved in ethyl acetate (100 mL), washed with saturated sodium chloride solution (100 mL) 3 times, dried over anhydrous sodium sulfate, filtered to remove the solid, and the filtrate was rotary evaporated to obtain a light yellow solid, i.e. 4-bromo-3-formylbenzoic acid methyl ester;

[0015] (3) Synthesis of 4-bromo-3-(1,3)dioxolan-2-yl-benzoic acid methyl ester:

[0016] Methyl 4-bromo-3-formylbenzoate (2.4 g, 10 mmol) was added to a 100 mL eggplant-shaped bottle, followed by the addition of p-toluenesulfonic acid (0.034 g, 0.2 mmol) and toluene (30 mL), and the mixture was heated to reflux in an oil bath at 140°C after adding a separator and a condenser to divert the water generated during the reaction. The reaction was monitored by thin layer chromatography, and the reaction was stopped after the raw material point disappeared; the mixture was cooled to room temperature, and the solid was obtained after concentration under reduced pressure. The solid was dissolved in 50 mL of ethyl acetate, and the organic phase was washed with saturated sodium bicarbonate (50 mL × 2) and chlorination solution (50 mL × 2), dried over anhydrous sodium sulfate for 1 h, the solid was removed by filtration, and the product was obtained after concentration under reduced pressure;

[0017] (4) Synthesis of methyl 2-(1,3)dioxolane-2-yl-4,4'-biphenyldicarboxylate:

[0018] 4-Bromo-3-(1,3)dioxolan-2-yl-benzoic acid methyl ester (2.7 g, 10 mmol), 4-methoxycarbonylphenylboronic acid (1.9 g, 1.1 mmol), palladium acetate (18 mg, 0.08 mmol) and sodium carbonate (2.1 g, 20 mmol) were placed in a 250 mL two-necked flask. After nitrogen was replaced, DMF (30 mL) was added under nitrogen protection and stirred at 90 ° C for 5 h. A large amount of palladium catalyst was removed by hot filtration, and then poured into water to precipitate solids. The mixture was extracted with ethyl acetate (100 mL × 3), and the extract was washed with saturated sodium chloride solution (200 mL × 3), and then dried with anhydrous sodium sulfate for 30 min. The solid was removed by filtration, and the filtrate was concentrated under reduced pressure. Column chromatography was used for purification, and the eluent was (ethyl acetate: petroleum ether = 1:8 to 1:4) to obtain a white solid, which was 2-(1,3)dioxolan-2-yl-4,4'-biphenyldicarboxylic acid methyl ester.

[0019] (5) Synthesis of 2-formyl-4,4'-biphenyldicarboxylic acid:

[0020] 2-(1,3)dioxolane-2-yl-4,4'-biphenyldicarboxylic acid methyl ester (2.6 g, 7.6 mmol) was added to a 100 mL eggplant-shaped bottle, and then MeOH (20 mL) and sodium hydroxide solution (1N, 10 mL) were added, and stirred at room temperature overnight; MeOH was removed by distillation under reduced pressure, and the pH value was adjusted to 3 with dilute hydrochloric acid (1N) to precipitate a solid, and the suspension was stirred in an oil bath at 50°C for 10 h; the solid was collected by suction filtration and dried in an oven at 70°C for 3 h to obtain a white solid, which was 2-formyl-4,4'-biphenyldicarboxylic acid;

[0021] (6) Synthesis of tertiary amine functionalized metal organic framework material (UiO-67-CH2-N(CH3)2):

[0022] Weigh 2-formyl-4,4'-biphenyldicarboxylic acid (152 mg, 0.56 mmol) and ZrCl4 (132 mg, 0.56 mmol) and put them into a 50 mL polytetrafluoroethylene liner, then add DMF (6 mL) and HCOOH (650 uL, 17 mmol), ultrasonically dissolve and clarify, seal in a stainless steel shell, and heat in a 120 ° C oven for 48 h; after naturally cooling to room temperature, filter the sample to remove the supernatant, transfer the remaining solid to a 50 mL centrifuge tube and add new DMF (10 mL) for ultrasonic washing, and then filter to remove the liquid, and repeat this twice; wash twice with MeOH in the same way, and the final material is vacuum dried in a vacuum oven at 80 ° C for 3 h to obtain the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3).

[0023] Preferably according to the present invention, the PFASs are perfluorobutyric acid (PFBA), perfluorohexanoic acid (PFHxA), perfluoroheptanoic acid (PFHpA), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUndA), perfluorobutane sulfonic acid (PFBS), perfluorohexane sulfonic acid (PFHxS) or perfluorooctane sulfonic acid (PFOS).

[0024] Preferably, according to the present invention, the solid phase extraction step is: before the solid phase extraction operation, the solid phase extraction column containing the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is activated with methanol and distilled water in sequence; then the water sample to be tested is passed through the solid phase extraction column containing the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2, and then the solid phase extraction column is rinsed with distilled water, and then the column is placed under a negative pressure of 80 kPa for 5 minutes to remove excess distilled water; then the eluent is eluted with an eluent, the eluate is collected, and after drying, it is re-dissolved with chromatographic pure methanol, passed through a 0.22 μm organic filter membrane, and stored.

[0025] Further preferably, a solid phase extraction column containing a tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is prepared according to the following method: the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is ground and crushed, added to methanol, ultrasonically dispersed evenly, and loaded into a 3mL solid phase extraction column empty column tube with a sieve plate placed at the bottom, and then a sieve plate is added to the adsorbent and pressed tightly, and a solid phase extraction column is prepared by wet loading, wherein the amount of the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is 5-40mg, preferably 30mg; the material of the solid phase extraction column is polypropylene;

[0026] Further preferably, the volumes of the activation methanol and distilled water are both 6 mL.

[0027] Further preferably, the flow rate of the water sample to be tested is 1-3 mL / min, further preferably 3 mL / min; the pH of the water sample to be tested is 1-9, further preferably 5.

[0028] Further preferably, the volume of distilled water used to rinse the solid phase extraction column is 10 mL.

[0029] Further preferably, the eluent is methanol (MA), acetonitrile (ACN), a methanol (MA) solution containing 0.1% ammonia water, an acetonitrile (ACN) solution containing 0.1% ammonia water, a methanol (MA) solution containing 0.1% acetic acid (HAc), an acetonitrile (ACN) solution containing 0.1% acetic acid (HAc), more preferably a methanol (MA) solution containing 0.1% ammonia water; the concentration of the ammonia water is 25-28wt%; the methanol (MA) solution containing 0.1% ammonia water refers to methanol The volume of aqueous ammonia in the (MA) solution is 0.1% of the volume of methanol, the acetonitrile (ACN) solution containing 0.1% aqueous ammonia means that the volume of aqueous ammonia in the acetonitrile (ACN) solution is 0.1% of the volume of acetonitrile, the methanol (MA) solution containing 0.1% acetic acid (HAc) means that the volume of acetic acid in the methanol (MA) solution is 0.1% of the volume of methanol, and the acetonitrile (ACN) solution containing 0.1% acetic acid (HAc) means that the volume of acetic acid in the acetonitrile (ACN) solution is 0.1% of the volume of acetonitrile.

[0030] More preferably, the volume of the eluent is 2-10 mL, and more preferably 8 mL.

[0031] More preferably, the drying is performed at 40° C. using a nitrogen gas flow to remove the solvent.

[0032] According to the preferred embodiment of the present invention, the liquid chromatography conditions are: C18 column: 150 mm × 2.1 mm, 3.5 μm;

[0033] Mobile phase A was 5 mmol / L ammonium acetate aqueous solution, and mobile phase B was acetonitrile; the flow rate was set at 0.3 mL / min, the column temperature was maintained at 30°C, and the injection volume was fixed at 5 μL; the gradient elution program was as follows: 0-1.0 min, 10% B; 1.0-2.0 min, 10-40% B; 2.0-10 min, 40-95% B, 10-11 min, 95% B, 11-16 min, 10% B;

[0034] The mass spectrometry conditions were as follows: in negative spray ionization mode, the ion source parameters included: capillary voltage -4500 V; temperature 550° C.; curtain gas, 40 psi; ion source gas 1.50 psi.

[0035] The technical features and beneficial effects of the present invention are as follows:

[0036] 1. The present invention utilizes the reductive amination reaction of aldehyde groups, uses 2-formyl-4,4'-biphenyldicarboxylic acid and ZrCl4 as reaction raw materials, and formic acid as a regulator and reducing agent. A MOF material with high adsorption capacity is synthesized by a solvent thermal method, and the prepared material is filled into an empty extraction column as a solid phase extraction adsorbent filler to prepare a solid phase extraction column, which is used for the extraction and enrichment of ten PFASs remaining in environmental water samples, and the enriched PFASs are detected and analyzed in combination with high performance liquid chromatography combined with tandem mass spectrometry (HPLC-MS / MS) technology. The solid phase extraction adsorbent prepared by the present invention has a large specific surface area and a rich porous structure, and can have multiple cross-actions such as hydrogen bonding and electrostatic effects with ten PFASs such as PFOA, PFOS, PFDA, and PFNA, and has good adsorption efficiency for the ten PFASs.

[0037] 2. The solid phase extraction column synthesized by the present invention has a simple preparation method, uses a small amount of adsorbent filler, and can be reused. The solid phase extraction separation method provided by the present invention solves the problem that the traditional PFASs separation and enrichment method has a long extraction time and uses a large amount of organic solvents to cause pollution, simplifies the sample pretreatment process, and embodies the concept of green chemistry; using high performance liquid chromatography detection, an analysis method for ten PFASs in water samples was established. The method is simple to operate, highly practical, and greatly saves analysis time and cost. The average recovery rate is 84.0-116.9%, the inter-day relative standard deviation (RSD) is 0.13-7.04%, and the intra-day RSD is 1.88-8.18%. , the extraction effect is good, the analysis results are accurate, and the reproducibility is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the synthesis route of UiO-67-CH2-N(CH3)2 of Example 1 and the SPE-HPLC-MS / MS detection technology process of the present invention.

[0039] Figure 2 This is a scanning electron microscope image of UiO-67-CH2-N(CH3)2 prepared in Example 1.

[0040] Figure 3 This is the FT-IR graph of UiO-67-CH2-N(CH3)2 prepared in Example 1.

[0041] Figure 4 This is the specific surface area and pore size analysis diagram of UiO-67-CH2-N(CH3)2 prepared in Example 1.

[0042] Figure 5This is a physical picture of the solid phase extraction column of the present invention after being filled with UiO-67-CH2-N(CH3)2 material adsorbent.

[0043] Figure 6 The results of solid phase extraction condition optimization in Example 2 are as follows: (a) water sample pH (b) sample flow rate (c) adsorbent mass (d) sample volume (e) eluent type (f) eluent volume. DETAILED DESCRIPTION

[0044] The present invention is further described below by means of specific examples, but is not limited thereto.

[0045] The material of the extraction column used in the embodiment is polypropylene, and the eluent used is a methanol (MA) solution containing 0.1% ammonia water, which means that the volume of ammonia water in the methanol (MA) solution is 0.1% of the volume of methanol, and an acetonitrile (ACN) solution containing 0.1% ammonia water means that the volume of ammonia water in the acetonitrile (ACN) solution is 0.1% of the volume of acetonitrile. The methanol (MA) solution containing 0.1% acetic acid (HAc) means that the volume of acetic acid in the methanol (MA) solution is 0.1% of the volume of methanol, and the acetonitrile (ACN) solution containing 0.1% acetic acid (HAc) means that the volume of acetic acid in the acetonitrile (ACN) solution is 0.1% of the volume of acetonitrile, wherein the concentration of ammonia water is 25wt%.

[0046] Example 1 Preparation of tertiary amine functionalized metal organic framework material (UiO-67-CH2-N(CH3)2)

[0047] (1) Synthesis of methyl 4-bromo-3-diacetoxymethylbenzoate:

[0048] Take methyl 4-bromo-3-methylbenzoate (4.6 g, 20 mmol) and dissolve it in glacial acetic acid (33 mL) and acetic anhydride (34 mL), cool it to 0°C in an ice-water bath, add concentrated sulfuric acid (5 mL), slowly add chromium trioxide (6 g, 60 mmol), after the reaction is complete by thin-layer chromatography, slowly pour in a large amount of ice water (500 mL), oscillate with ultrasound for 2 h, collect the precipitated solid by filtration, wash the filter cake with water, and dry the solid at 70°C for 3 h to obtain a light yellow solid, which is methyl 4-bromo-3-diacetoxymethylbenzoate;

[0049] (2) Synthesis of methyl 4-bromo-3-formylbenzoate:

[0050] 4-bromo-3-diacetoxymethylbenzoic acid methyl ester (4.2 g, 11 mmol) was placed in a 250 mL eggplant-shaped bottle, and then THF (50 mL) and HCI (1N, 20 mL) were added in sequence. The reaction solution was stirred at 90°C under nitrogen protection, and the reaction was monitored by thin layer chromatography. When the raw material point disappeared, the reaction was stopped, and the mixture was distilled under reduced pressure. The obtained mixture was dissolved in ethyl acetate (100 mL), washed with saturated sodium chloride solution (100 mL) 3 times, dried over anhydrous sodium sulfate, filtered to remove the solid, and the filtrate was rotary evaporated to obtain a light yellow solid, i.e. 4-bromo-3-formylbenzoic acid methyl ester;

[0051] (3) Synthesis of 4-bromo-3-(1,3)dioxolan-2-yl-benzoic acid methyl ester:

[0052] Methyl 4-bromo-3-formylbenzoate (2.4 g, 10 mmol) was added to a 100 mL eggplant-shaped bottle, followed by the addition of p-toluenesulfonic acid (0.034 g, 0.2 mmol) and toluene (30 mL), and the mixture was heated to reflux in an oil bath at 140°C after adding a separator and a condenser to divert the water generated during the reaction. The reaction was monitored by thin layer chromatography, and the reaction was stopped after the raw material point disappeared; the mixture was cooled to room temperature, and the solid was obtained after concentration under reduced pressure. The solid was dissolved in 50 mL of ethyl acetate, and the organic phase was washed with saturated sodium bicarbonate (50 mL × 2) and chlorination solution (50 mL × 2), dried over anhydrous sodium sulfate for 1 h, the solid was removed by filtration, and the product was obtained after concentration under reduced pressure;

[0053] (4) Synthesis of methyl 2-(1,3)dioxolane-2-yl-4,4'-biphenyl dicarboxylate:

[0054] 4-Bromo-3-(1,3)dioxolan-2-yl-benzoic acid methyl ester (2.7 g, 10 mmol), 4-methoxycarbonylphenylboronic acid (1.9 g, 1.1 mmol), palladium acetate (18 mg, 0.08 mmol) and sodium carbonate (2.1 g, 20 mmol) were placed in a 250 mL two-necked flask. After nitrogen was replaced, DMF (30 mL) was added under nitrogen protection and stirred at 90 ° C for 5 h. A large amount of palladium catalyst was removed by hot filtration, and then poured into water to precipitate solids. The mixture was extracted with ethyl acetate (100 mL × 3), and the extract was washed with saturated sodium chloride solution (200 mL × 3), and then dried with anhydrous sodium sulfate for 30 min. The solid was removed by filtration, and the filtrate was concentrated under reduced pressure. Column chromatography was used for purification, and the eluent was (ethyl acetate: petroleum ether = 1:8 to 1:4) to obtain a white solid, which was 2-(1,3)dioxolan-2-yl-4,4'-biphenyldicarboxylic acid methyl ester.

[0055] (5) Synthesis of 2-formyl-4,4'-biphenyldicarboxylic acid:

[0056] 2-(1,3)dioxolane-2-yl-4,4'-biphenyldicarboxylic acid methyl ester (2.6 g, 7.6 mmol) was added to a 100 mL eggplant-shaped bottle, and then MeOH (20 mL) and sodium hydroxide solution (1N, 10 mL) were added, and stirred at room temperature overnight; MeOH was removed by distillation under reduced pressure, and the pH value was adjusted to 3 with dilute hydrochloric acid (1N) to precipitate a solid, and the suspension was stirred in an oil bath at 50°C for 10 h; the solid was collected by suction filtration and dried in an oven at 70°C for 3 h to obtain a white solid, which was 2-formyl-4,4'-biphenyldicarboxylic acid;

[0057] (6) Synthesis of tertiary amine functionalized metal organic framework material (UiO-67-CH2-N(CH3)2):

[0058] Weigh 2-formyl-4,4'-biphenyldicarboxylic acid (152 mg, 0.56 mmol) and ZrCl4 (132 mg, 0.56 mmol) and put them into a 50 mL polytetrafluoroethylene liner, then add DMF (6 mL) and HCOOH (650 uL, 17 mmol), ultrasonically dissolve and clarify, seal in a stainless steel shell, and heat in a 120 ° C oven for 48 h; after naturally cooling to room temperature, filter the sample to remove the supernatant, transfer the remaining solid to a 50 mL centrifuge tube and add new DMF (10 mL) for ultrasonic washing, and then filter to remove the liquid, and repeat this twice; wash twice with MeOH in the same way, and the final material is vacuum dried in a vacuum oven at 80 ° C for 3 h to obtain the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2.

[0059] The synthesis route of UiO-67-CH2-N(CH3)2 and the sample pretreatment process are as follows Figure 1 , and the synthesized UiO-67-CH2-N(CH3)2 material was characterized. Figure 2 This is a scanning electron microscope (SEM) image of UiO-67-CH2-N(CH3)2, which shows that the MOF material is a regular octahedron with an average diameter of about 5μm; Figure 3 The chemical bonds in the structure of UiO-67-CH2-N(CH3)2 were characterized and analyzed by Fourier transform infrared spectroscopy (FT-IR). -1 A new absorption peak of CN bond appears at the position, indicating the formation of amine group; and the MOF material is subjected to N2 adsorption and desorption experiment, and its adsorption and desorption curve is obtained as follows Figure 4 As shown in the figure, the specific surface area of ​​UiO-67-CH2-N(CH3)2 was calculated using the BET calculation method, and the specific surface area was 291 m 2 / g. Figure 4In the internal figure, we obtained the pore size distribution curve of UiO-67-CH2-N(CH3)2, and the pore size of CMP calculated by HK method was 3.3nm. The above results prove that UiO-67-CH2-N(CH3)2 has a high specific surface area and mesoporous structure, and is an ideal material for adsorbing PFASs.

[0060] Example 2: Preparation of solid phase extraction column and optimization of solid phase extraction procedure

[0061] 2.1 Optimizing the optimal values ​​of each factor for the highest extraction recovery of ten PFASs

[0062] The tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 prepared in Example 1 was used as a solid phase extraction adsorbent, and ten PFASs, including PFBA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUndA, PFBS, PFHxS, and PFOS, were selected as target compounds. In order to achieve the best enrichment efficiency of PFASs, several important parameters affecting the results in the SPE extraction process, extraction conditions (pH, sample flow rate, adsorbent dosage and sample volume) and elution conditions (eluent type and eluent volume) were optimized one by one, and the following steps were followed:

[0063] (i) Preparation of solid phase extraction column

[0064] The tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 adsorbent prepared in Example 1 was added to 10 mL of methanol, ultrasonically dispersed evenly, and added to a 3 mL solid phase extraction small column empty column tube with a sieve plate at the bottom, and then another sieve plate was added to the adsorbent and pressed tightly, and a solid phase extraction column was prepared by wet loading, as shown in the photo. Figure 5 shown.

[0065] (ii) 6 mL of methanol and 6 mL of distilled water were used to activate the solid phase extraction column containing the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2;

[0066] (iii) PFBA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUndA, PFBS, PFHxS and PFOS were added to water to prepare a water sample with a concentration of 50 μg / L; the prepared water sample was passed through a solid phase extraction column containing a tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2; the solid phase extraction column was then rinsed with 10 mL of distilled water and then placed under a negative pressure of 80 kPa for 5 minutes to remove excess distilled water; the target compound retained on the UiO-67-CH2-N(CH3)2 material was eluted with an eluent, the eluate was collected, dried at 40°C using a nitrogen gas flow to remove the solvent, and finally re-dissolved with 1 mL of chromatographic grade methanol, filtered through a 0.22 μm organic filter membrane, and stored.

[0067] (iv) Liquid chromatography-tandem mass spectrometry test conditions

[0068] Liquid chromatography conditions: C18 column: 150 mm × 2.1 mm, 3.5 μm; mobile phase A is 5 mmol / L ammonium acetate aqueous solution, mobile phase B is acetonitrile; flow rate is set at 0.3 mL / min, column temperature is maintained at 30 °C, injection volume is fixed at 5 μL; gradient elution program is as follows:

[0069] 0-1.0min, 10%B, 90%A; 1.0-2.0min, 10-40%B, 90-60%A; 2.0-10min, 40-95%B, 60-5%A; 10-11min, 95%B, 5%A; 11-16min, 10%B, 90%A.

[0070] The mass spectrometry conditions were as follows: in negative spray ionization mode, the ion source parameters included: capillary voltage -4500 V; temperature 550° C.; curtain gas, 40 psi; ion source gas 1.50 psi.

[0071] (1) Effect of water sample pH on extraction recovery

[0072] The pH value of the solution affects the existence form of the target analyte, and thus greatly affects the extraction efficiency. In step (iii), a 37 wt% concentrated hydrochloric acid solution or a 25% ammonia solution is used to adjust the pH value of the water sample to be tested to 1, 3, 5, 7, and 9, respectively; other conditions are: the amount of adsorbent is 30 mg, the sample volume is 50 mL, the sample flow rate is 3 mL / min, and methanol (MA) containing 0.1% ammonia is used as the eluent, and the eluent volume is 8 mL. Figure 6(A) shows that the recovery rate of PFASs increases at pH 4-5. This is because under acidic conditions, the material is positively charged, and the negative charge of PFASs under this condition interacts electrostatically with the positive charge of UiO-67-CH2-N(CH3)2, enhancing the adsorption effect. On this basis, pH 5 is the best condition.

[0073] (2) Study on the effect of sample flow rate on extraction recovery

[0074] This example investigates the flow rate of 1-5 mL / min, and the sample flow rate in step (iii) is adjusted to 1, 2, 3, 4, and 5 mL / min, respectively; other conditions are: the amount of adsorbent is 30 mg, the sample pH is 5, the sample volume is 50 mL, MA containing 0.1% ammonia water is used as the eluent, and the eluent volume is 8 mL: Figure 6 (B) It can be seen that the flow rate has little effect in the range of 1-3 mL / min. Then, the recovery rate decreases at 4 mL / min. Therefore, a flow rate of 3 mL / min is considered optimal in SPE.

[0075] (3) Effect of adsorbent dosage on extraction recovery rate

[0076] The amount of adsorbent in the solid phase extraction column is an important parameter that needs to be optimized. If the amount of adsorbent is too little, the adsorption is not thorough and the extraction and enrichment efficiency is low; if the amount of adsorbent is too large, it may cause material waste. The amount of adsorbent of 5-40 mg was studied, that is, the amount of adsorbent in step (i) was adjusted to 5, 10, 20, 30, and 40 mg, respectively. The other conditions were: sample pH = 5, sample volume 50 mL, sample flow rate 3 mL / min, methanol (MA) containing 0.1% ammonia water as the eluent, and the eluent volume was 8 mL. By Figure 6 (C) It can be seen that the solid phase extraction efficiency increased significantly at 5-30 mg, and when it continued to increase to 40 mg, the efficiency did not change significantly. Finally, the optimal amount of adsorbent was set to 30 mg.

[0077] (4) Effect of sample volume on extraction recovery

[0078] This example investigates the effect of different sample volumes (50-250 mL) on the recovery rate of PFASs. In step (iii), the sample volumes were adjusted to 50, 100, 150, 200, and 250 mL, respectively. Other conditions were: adsorbent dosage was 30 mg, sample pH = 5, sample flow rate was 3 mL / min, MA containing 0.1% ammonia water was used as the eluent, and the eluent volume was 8 mL. The results showed that the recovery rate did not change with the change of sample volume. Therefore, a sample volume of 200 mL was selected to obtain highly sensitive analysis results. When the sample solution volume is larger, a higher enrichment multiple can be obtained.

[0079] (5) Effect of eluent type on extraction recovery rate

[0080] The effects of different eluents such as methanol (MA), acetonitrile (ACN), MA containing 0.1% ammonia, ACN containing 0.1% ammonia, MA containing 0.1% acetic acid (HAc), and ACN containing 0.1% HAc were investigated; other conditions were: adsorbent dosage 30 mg, sample pH = 5, sample volume 50 mL, sample flow rate 3 mL / min, and eluent volume 8 mL. Figure 6 (E) shows the results that MA containing 0.1% ammonia water was selected as the final elution solvent, which had the highest recovery rate for PFASs.

[0081] (6) Effect of eluent volume on extraction recovery

[0082] Optimization of the eluent volume is very necessary. Too little eluent volume will lead to incomplete desorption and low enrichment efficiency. Using too much eluent may cause contamination of organic reagents. In this experiment, 2-10mL (2, 4, 6, 8, 10mL) eluent volumes were tested; other conditions were: adsorbent dosage was 30mg, sample pH = 5, sample volume was 50mL, sample flow rate was 3mL / min, and MA containing 0.1% ammonia water was used as the eluent; Figure 6 As shown in (F), when the volume of the eluent increased from 2 mL to 8 mL, the recovery rate increased, and when it exceeded 8 mL, the recovery rate did not change significantly. Therefore, in subsequent experiments, the optimal volume of the eluent was 8 mL.

[0083] Therefore, the optimal experimental conditions for solid phase extraction enrichment of ten PFASs by UiO-67-CH2-N(CH3)2 material are as follows: adsorbent dosage is 30 mg, sample pH = 5, sample volume is 200 mL, sample flow rate is 3 mL / min, MA containing 0.1% ammonia water is used as eluent, and the eluent volume is 8 mL.

[0084] 2.2 Linear correlation parameters, detection limits and precision of the method for determination of ten PFASs

[0085] The specific steps are as follows:

[0086] (1) 30 mg of the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 adsorbent prepared in Example 1 was added to 10 mL of methanol, dispersed evenly by ultrasonication, and added to a 3 mL solid phase extraction small column empty column tube with a sieve plate at the bottom. Then, another sieve plate was added to the adsorbent and pressed tightly, and a solid phase extraction column was prepared by wet loading.

[0087] (2) Before the solid phase extraction operation, the solid phase extraction column containing the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 was activated with 6 mL of methanol and 6 mL of distilled water respectively.

[0088] (3) PFBA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUndA, PFBS, PFHxS, and PFOS were added to water to prepare a solution with a concentration of 50 μg / L. The pH was adjusted to 5 with a 37 wt% concentrated hydrochloric acid solution to obtain a water sample with a pH of 5.0 and a concentration of 50 μg / L. 200 mL of the water sample was passed through a tertiary amine-functionalized metal organic framework material UiO-67-CH2-N( CH3)2 material solid phase extraction column; then rinse the solid phase extraction column with 10mL distilled water to eliminate potential interfering matrix on the SPE column, and the SPE column is under negative pressure of 80kPa for 5 minutes to remove excess distilled water; then, elute with 8mL of methanol (MA) solution containing 0.1% ammonia water, collect the eluate, and then use nitrogen gas flow to dry and concentrate the eluate at 40°C to remove the solvent. Finally, dissolve the extract with 1mL of chromatographic pure methanol, pass through a 0.22μm organic phase filter membrane, and store it in a sample bottle for testing.

[0089] (4) Liquid chromatography-tandem mass spectrometry was used for detection. The specific detection conditions were as follows:

[0090] The HPCL detection conditions were: C18 column: 150 mm × 2.1 mm, 3.5 μm;

[0091] Mobile phase A was 5 mmol / L ammonium acetate aqueous solution, and mobile phase B was acetonitrile; the flow rate was set at 0.3 mL / min, the column temperature was maintained at 30°C, and the injection volume was fixed at 5 μL; the gradient elution program was as follows: 0-1.0 min, 10% B, 90% A; 1.0-2.0 min, 10-40% B, 90-60% A; 2.0-10 min, 40-95% B, 60-5% A; 10-11 min, 95% B, 5% A; 11-16 min, 10% B, 90% A;

[0092] The mass spectrometry conditions were as follows: in negative spray ionization mode, the ion source parameters included: capillary voltage -4500 V; temperature 550° C.; curtain gas, 40 psi; ion source gas 1.50 psi.

[0093] The limit of detection (LOD) and limit of quantification (LOQ) were evaluated based on signal-to-noise ratios of 3:1 and 10:1. The linearity of the calibration was determined by plotting the peak area versus theoretical concentration in the range of 0.2-400 ng / L. Intra-day and inter-day precision were determined by analyzing sample solutions replicated five times per day and replicated over three consecutive days.

[0094] Table 1 summarizes the validation results of the SPE-HPLC-MS / MS method. The method showed excellent linearity from 0.2 to 400 ng / L. The correlation coefficients (r) for PFASs were between 0.992 and 0.999. The detection limit was 0.02-0.88 ng / L, and the quantification limit was 0.06-2.54 ng / L. The intra-day relative standard deviation (RSD) of PFASs was 0.13-7.04%, and the intra-day RSD was 1.88-8.18%. These results indicate that SPE combined with LC-MS / MS analysis based on UiO-67-CH2-N(CH3)2 is a highly reliable and sensitive method for analyzing trace concentrations of PFASs.

[0095] Table 1 Methodological parameters of ten PFASs

[0096]

[0097] Example 3: Solid phase extraction combined with HPCL-MS / MS to detect the residual amounts of ten PFASs in actual samples

[0098] The SPE-LC-MS / MS for determination of UiO-67-CH2-N(CH3)2 allows the analysis of the residues of 10 PFASs in environmental water samples (snow water, river water, groundwater) under optimal conditions. After collecting 3 water samples, they are filtered with a rapid qualitative filter paper with a pore size of 80-120 μm, and then filtered with a 0.45 μm filter membrane; the filtered water samples are determined by the method described in Example 2, and the accuracy is tested by the method described in Example 2. Ten PFASs concentrations of 1.25 μg / L, 5 μg / L, and 25 μg / L are prepared respectively. The actual water samples of three concentrations of low, medium, and high concentrations are tested for spiked recovery. Each concentration point is measured 3 times, and the average value, relative standard deviation, and spiked recovery of the three measurements are calculated; wherein, no PFASs residues are shown in the water samples. When the tap water concentration was 1.25, 5.0, and 25.0 ng / L, the recovery rates of snow water were 84.0-113.6%, river water was 84.7-108.3%, and groundwater was 85.3-116.9%. Therefore, the extraction effect of this embodiment was good, the measurement results were accurate, and the reproducibility was good. The applicability and effectiveness of the established SPE-LC-MS / MS method based on UiO-67-CH2-N(CH3)2 for the quantitative analysis of trace PFASs levels in environmental water samples were revealed.

[0099] Table 2 Analysis results of PFASs in actual water samples

[0100] Table 3 Analysis results of PFASs in actual water samples

[0101]

[0102] a The spiked concentration was 1.25 ng / L, b The spiked concentration was 5 ng / L, c The spiked concentration was 25 ng / L, and d was not detected.

[0103] Example 4: Comparison of adsorption effects between UiO-67-CH2-N(CH3)2 and UiO-67 materials

[0104] (1) Synthesis of metal organic framework materials (UiO-67) without tertiary amine functional groups:

[0105] Take 4,4'-biphenyldicarboxylic acid (43.7 mg), ZrCl4 (45 mg) and acetic acid (20 μL), dissolve in N,N-dimethylformamide (15 mL), transfer the solution to a 50 mL polytetrafluoroethylene-lined stainless steel reactor, seal and heat to 120 ° C, and react for 24 hours. After the reaction is completed, wait for the reactor to cool to room temperature, and the resulting precipitate is washed three times by centrifugation with N,N-dimethylformamide, and then dried at 100 ° C for 5 hours to obtain a white-gray solid, which is UiO-67.

[0106] (2) Comparison of adsorption effects between UiO-67-CH2-N(CH3)2 and UiO-67 materials

[0107] The UiO-67 material was subjected to the same optimal solid phase extraction conditions: adsorbent dosage was 30 mg, sample pH = 5, sample volume was 200 mL, sample flow rate was 3 mL / min, MA containing 0.1% ammonia water was used as eluent, and the eluent volume was 8 mL. The adsorption effects of ten PFASs were measured as shown in the following table:

[0108] Table 4 Comparison of the adsorption effects of ten PFASs by UiO-67-CH2-N(CH3)2 and UiO-67 materials

[0109]

[0110] It can be seen from the table that the adsorption efficiency of UiO-67-CH2-N(CH3)2 for ten PFASs is significantly higher than that of UiO-67. The tertiary amine functional group constructs an ion response system, thereby forming multiple active sites with electron-withdrawing ability, achieving the effect of efficient and directional adsorption of perfluorinated compounds, and fully stimulating various adsorption mechanisms such as electrostatic effect, pore filling, and hydrophobic effect, so that the adsorption system has more electrostatic adsorption sites, greatly improving the adsorption performance of perfluorinated compounds.

[0111] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for analyzing and detecting PFASs in environmental water samples, characterized in that: The analytical detection method uses a tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 as a solid phase extraction adsorbent for solid phase extraction, and then combines it with liquid chromatography-tandem mass spectrometry to detect PFASs in environmental water samples.

2. The method for analyzing and detecting PFASs in environmental water samples according to claim 1, characterized in that: The PFASs are PFBA, PFHxA, PFHpA, PFOA, PFNA, PFDA, PFUndA, PFBS, PFHxS or PFOS.

3. The method for analyzing and detecting PFASs in environmental water samples according to claim 1, characterized in that: The solid phase extraction step is: before the solid phase extraction operation, the solid phase extraction column equipped with the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is activated with methanol and distilled water in sequence; then the water sample to be tested passes through the solid phase extraction column equipped with the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2, and then the solid phase extraction column is rinsed with distilled water, and then the column is placed under a negative pressure of 80kpa for 5 minutes to remove excess distilled water; then the eluent is eluted with an eluent, the eluate is collected, and after drying, it is redissolved with chromatographic pure methanol, and after passing through a 0.22μm organic filter membrane, it is stored.

4. The method for analyzing and detecting PFASs in environmental water samples according to claim 3, characterized in that: A solid phase extraction column containing a tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is prepared according to the following method: the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is ground and crushed, added to methanol, and evenly dispersed by ultrasonication, and then loaded into a 3mL solid phase extraction column empty column tube with a sieve plate placed at the bottom, and then another sieve plate is added to the adsorbent and pressed tightly, and a solid phase extraction column is prepared by wet loading, wherein the amount of the tertiary amine functionalized metal organic framework material UiO-67-CH2-N(CH3)2 is 5-40mg, preferably 30mg; the material of the solid phase extraction column is polypropylene.

5. The method for analyzing and detecting PFASs in environmental water samples according to claim 3, characterized in that: The volumes of the activation methanol and distilled water were both 6 mL.

6. The method for analyzing and detecting PFASs in environmental water samples according to claim 3, characterized in that: The flow rate of the water sample to be tested is 1-3 mL / min, preferably 3 mL / min; the pH of the water sample to be tested is 1-9, preferably 5.

7. The method for analyzing and detecting PFASs in environmental water samples according to claim 3, characterized in that: The volume of distilled water used to rinse the solid phase extraction column was 10 mL; The eluent is methanol, acetonitrile, methanol solution containing 0.1% ammonia water, acetonitrile solution containing 0.1% ammonia water, methanol solution containing 0.1% acetic acid, acetonitrile solution containing 0.1% acetic acid, more preferably methanol solution containing 0.1% ammonia water; the concentration of the ammonia water is 25-28wt%.

8. The method for analyzing and detecting PFASs in environmental water samples according to claim 3, characterized in that: The volume of the eluent is 2-10 mL, preferably 8 mL; The drying step is to use a nitrogen gas flow to dry at 40° C. to remove the solvent; the volume of chromatographically pure methanol used for re-dissolution is 1 mL.

9. The method for analyzing and detecting PFASs in environmental water samples according to claim 1, characterized in that: Liquid chromatography conditions were: C18 column: 150 mm × 2.1 mm, 3.5 μm; Mobile phase A was 5 mmol / L ammonium acetate aqueous solution, and mobile phase B was acetonitrile; the flow rate was set at 0.3 mL / min, the column temperature was maintained at 30°C, and the injection volume was fixed at 5 μL; the gradient elution program was as follows: 0-1.0 min, 10% B; 1.0-2.0 min, 10-40% B; 2.0-10 min, 40-95% B, 10-11 min, 95% B, 11-16 min, 10% B.

10. The method for analyzing and detecting PFASs in environmental water samples according to claim 1, characterized in that: In negative spray ionization mode, the ion source parameters included: capillary voltage -4500 V; temperature 550°C; curtain gas, 40 psi; ion source gas, 1.50 psi.

Citation Information

Patent Citations

  • Method for detecting five neonicotinoid insecticides in environmental water sample

    CN117907493A

  • Synchronous detection method for perfluoroalkyl / polyfluoroalkyl substances in water sample

    CN118330092A